Common Law among the Statutes: The Lord Cooke Lecture 2007 - Burrows, John (Victoria University of Wellington Law Review, 2008)
This article is based on the 6th Lord Cooke Lecture, delivered in the Law School of the Victoria University of Wellington on 5 December 2007. The author discusses the relationship between common law and statute, a topic in which Lord Cooke had a real interest and on which he and the author discussed in person.